The discovery, biodiversity and conservation of Mabu forest—the largest medium-altitude rainforest in southern Africa. Issue 2 (April 2014) - Bayliss, Julian; Timberlake, Jonathan; Branch, William; Bruessow, Carl; Collins, Steve; Congdon, Colin; Curran, Michael; de Sousa, Camila; Dowsett, Robert; Dowsett-Lemaire, Francoise; Fishpool, Lincoln; Harris, Timothy; et al.
Abstract The montane inselbergs of northern Mozambique have been comparatively little-studied, yet recent surveys have shown they have a rich biodiversity with numerous endemic species. Here we present the main findings from a series of scientific expeditions to one of these inselbergs, Mt Mabu, and discuss the conservation implications. Comprehensive species lists of plants, birds, mammals and butterflies are presented. The most significant result was the discovery of a c. 7, 880 ha block of undisturbed rainforest, most of it at medium altitude (900–1, 400 m), a forest type that is not well represented elsewhere. It is possibly the largest continuous block of this forest type in southern Africa. To date, 10 new species (plants, mammals, reptiles and butterflies) have been confirmed from Mt Mabu, even though sampling effort for most taxonomic groups has been low. The species assemblages indicate a relatively long period of isolation and many species found are at the southern limit of their range. Conservationists are now faced with the challenge of how best to protect Mt Mabu and similar mountains in northern Mozambique, and various ways that this could be done are discussed.